Potret Komunikasi Antarbudaya Muslim dan Hindu dengan Adat Ogoh-Ogoh Desa Sukoreno - Kusumawati, Dina; Setiawan, Iwan (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to explore how the Muslim community and the ogoh-ogoh traditional culture in Sukoreno Village, located in Sukowono District, Jember Regency, East Java, Indonesia, interact socially. Using a qualitative sociological approach, this research employs religious leaders, ogoh-ogoh traditional leaders, and the village head as key informants and primary data sources. Meanwhile, other elements within these two communities serve as secondary data sources. The findings indicate that communication between the Muslim community and the ogoh-ogoh traditionalists involves both verbal and non-verbal means, with various network patterns such as primary, secondary, circular, and multidirectional. Social cohesion among the communities is achieved through their ability to use adaptive or integrative strategies. Additionally, a high level of intercultural communication competence enables these communities to live harmoniously and support each other.